Mild Cognitive Impairment in de novo Parkinson's Disease: Selective Attention Deficit as Early Sign of Neurocognitive Decay - Cammisuli, Davide Maria; Pagni, Cristina; Palermo, Giovanni; Frosini, Daniela; Bonaccorsi, Joyce; Radicchi, Claudia; Cintoli, Simona; Tommasini, Luca; Tognoni, Gloria; Ceravolo, Roberto; Bonuccelli, Ubaldo (Frontiers in Psychology, 2021)
Background: In the present study, we aimed to better investigate attention system profile of Parkinson's disease-Mild Cognitive Impairment (PD-MCI) patients and to determine if specific attentional deficits are associated with 123I-FP-CIT SPECT. Methods: A total of 44 de novo drug-naïve PD patients [(27 with normal cognition (PD-NC) and 17 with MCI (PD-MCI)], 23 MCI patients and 23 individuals with subjective cognitive impairment (SCI) were recruited at the Clinical Neurology Unit of Santa Chiara hospital (Pisa University Medical School, Italy). They were assessed by a wide neuropsychological battery, including Visual Search Test (VST) measuring selective attention. Performances among groups were compared by non-parametric tests (i.e., Kruskal-Wallice and Mann-Whitney, Bonferroni corrected). Further, Spearman’s rank correlations were performed to explore the association between neuropsychological variables and 123I-FP-CIT SPECT data in PD subgroup. Results: PD-MCI patients performed worse on VST than patients with PD-NC (p= .002), patients with MCI and individuals with SCI (p < .001). The performance of PD-MCI patients on VST significantly correlated with caudate nucleus 123I-FP-CIT SPECT uptake (rho= .582, p < .05), whereas a negative correlation between such test and 123I-FP-CIT SPECT uptake in the left putamen (rho= -.529, p < .05) was found in PD-NC patients. Conclusions: We suggest that selective attention deficit might be a trigger of cognitive decay in de novo PD-MCI patients. The VST should be routinely used to detect attentional deficits in hospital clinical practice, in the light of its closely association with dopamine depletion of basal ganglia in mildly impaired PD patients.